ASME 2021 Power Conference 2021
DOI: 10.1115/power2021-65714
|View full text |Cite
|
Sign up to set email alerts
|

First Numerical Evaluation of the Thermal Performance of a Tubular Receiver Equipped With Raschig Rings for CSP Applications

Abstract: Porous media are typically capable to enhance heat transfer, at the cost of an increase of the pressure drop, mainly in view of the huge increase in the surface wetted by the fluid. In this work, a tubular receiver for CSP applications, partly filled with a porous medium constituted by a packed bed of copper Raschig Rings is investigated for the first time. The analysis, carried out numerically, aims at studying in detail the mechanisms of the heat transfer from the wall to the gaseous heat transfer fluid (air… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Thus, loose packing spots can provide enough space for vortex and high-speed flow formations, while stagnation zones can be observed whiten the dense packing areas. Results follow the conclusions derived in other works (Ebadi et al, 2021).…”
Section: Resultssupporting
confidence: 91%
“…Thus, loose packing spots can provide enough space for vortex and high-speed flow formations, while stagnation zones can be observed whiten the dense packing areas. Results follow the conclusions derived in other works (Ebadi et al, 2021).…”
Section: Resultssupporting
confidence: 91%
“…Wang et al [7] conducted a numerical investigation involving twisted porous tape and nanofluids in tubes, revealing substantial efficiency and heat exchange improvements when employing porous twisted tape, nanofluids, and triangular tubes. Experimental evidence supports the effectiveness of incorporating porous medium inserts, both inside [8] and outside [9] the absorber, in enhancing heat transfer. However, numerical studies in this regard remain limited.…”
Section: Introductionmentioning
confidence: 73%
“…The combination of nanofluids and porous medium inserts holds significant promise for enhancing thermal performance, as supported by several studies [6][7][8][9][10][11]. El-Shorbagy et al [6] demonstrated that optimal heat transfer in partially filled trapezoidal channels with porous media occurs when the aspect ratio is set at 0.3, and 90% of the channel is filled with porous material.…”
Section: Introductionmentioning
confidence: 94%